(untitled) (Journal of the College of Basic Education, 2025)
The subject (Theories of Music Analysis) is considered one of the highly specialized subjects in music science, and therefore teaching it in the third stage places strong pressure on the student, and from here comes the problem of the research. As for its importance, it lies in the weak balance between the student’s mentality at this stage and this scientific subject, as We find a noticeable difference between the two, Therefore, the research aims to raise the teaching of this subject to the fifth or fourth stage, where the student has begun to delve deeply into the music specialization and collect enough priorities and scientific foundations that help him comprehend, digest, and comprehend the concepts it contains. The temporal limits of the research were the academic year 2021/2022 As for the spatial boundaries, they were at the Institute of Fine Arts for Girls in Baqubah within the Diyala Governorate Education Directorate. The third-stage students at the institute were chosen as a sample for the research, as they are part of the research community, which is the institute itself. The researcher also adopted the form of a written questionnaire as a means of collecting data that reinforces the reason for choosing This topic is researched, The results of the analysis were largely consistent with that reason, and the conclusions ultimately concluded that there was an actual desire among the students to raise the teaching of music analysis theories to a higher level, and this is what the researcher recommended at the conclusion of her research.